(untitled) (Bangladesh Journal of Agricultural Research, 2011)
A field experiment on cabbage (Brassica oleracea var. capitata) comprising two plant spacings viz. 60 × 40 cm and 60 × 45 cm and ten hybrid cabbage varieties viz. Green Rich, Green-621, Green Coronet, Summer Warrior, Rare Ball, Atlas- 70, Southern treasure, Laurels, K-K Cross and K-S Cross was conducted during 15 October to 12 February of 2005-07 at the Agricultural Research Station, Raikhali, Rangamati Hill District to find out the optimum plant spacing and suitable cabbage variety(s). The wider spacing of 60 × 45 cm resulted in significantly maximum number of folded leaves and head weight (without unfolded leaves) in comparison to closer spacing of 60 × 30 cm. The variety Green Coronet showed the highest plant height, number of unfolded leaves, length of the biggest loose leaf, widest leaf, head height, and head weight (with unfolded leaves).This variety took the highest duration (119 days), while Green- 621 took the lowest duration for harvest (105 days). Although Green Coronet grew vigorously, it did not produce the highest head yield. All the varieties had good head compactness except Laurels and Green Coronet which had medium and less compactness, respectively. The combination of 60 × 30 cm spacing with variety Southern Treasure and K-S cross produced the highest head diameter, but wider spacing of 60 × 45 cm accompanied by Southern Treasure produced the highest head weight without unfolded leaves followed by K- K Cross in both the years. The pooled analysis showed the highest marketable head yield (73.32 t/ha) in the combination of 60 x 40 cm spacing with K- K Cross, which was closely followed by Southern Treasure (71.71 t/ha) and Laurels (71.56 t/ha). The variety Green-621 was found suitable for early harvest with reasonable yield (67.82 t/ha). Keywords: Cabbage; Brassica oleracea var. Capitata; hybrid variety; spacing; head yield; Rangamati. DOI: http://dx.doi.org/10.3329/bjar.v36i3.9277 BJAR 2011; 36(3): 495-506